Le Sida en Afrique - Goubau, Patrick; Surmont, Ignace; Piot, Peter (Afrika Focus, 1987)
AIDS (Acquired Immunization Deficiency Syndrome), first described in I 9 8 I in the United States, is at present ascertained on every continent. Since its description, our knowledge about AIDS has advanced with giant steps, with regard to its causal agent, clinical image, biological effects and epidemiology. Although it is everywhere the same disease, its epidemiology and impact on society vary from one continent to another depending on the human, social and economic conditions of the countries which are affected. The first African cases were noticed in 1983. Since then the presence of AIDS has been confirmed in numerous sub-Saharan African countries. Our goal is to present here some characteristic features of the AIDS-epidemic in Africa and to offer some points of reflection for future action. KEYWORDS : AIDS, Africa, diagnostics, epidemiology, treatment